Phenotypic characteristics of human monocytes undergoing transendothelial migration - Grisar, Johannes (BioMed Central, 2001)
In our study we characterised the immunophenotype of monocytes that migrated through an endothelial cell (EC) monolayer in vitro. We found that monocyte migration led to an enhanced expression of CD11a, CD33, CD45RO, CD54 [intercellular cell-adhesion molecule (ICAM)-1] and human leucocyte antigen-DR. The most striking increase was observed for ICAM-1 when ECs were activated with tumour necrosis factor-α and interleukin-1α. The results of our study indicate the following: (1) there is a characteristic immunophenotype on the surface of monocytes after transendothelial migration; (2) this phenotype seems to be induced by interactions between monocytes and ECs; and (3) this change is enhanced by the pretreatment of ECs with cytokines. Taken together, the results suggest that local cytokine production activating ECs is sufficient to enhance monocyte migration and that this, in turn, can induce changes consistent with an activated phenotype known to be interactive between antigen-presenting cells and T cells. These results have implications for our pathogenetic insights into rheumatoid arthritis.